Pre-Service Elementary Teachers' Environmental Identities and Materialistic Tendencies Towards The Environment: Moral Reasoning Based Environmental Education - Esra Saraç; Rabia Sarıkaya (Anı Publishing, 2020)
Theaim of this study is to examine the effect of moral reasoning based environmental education on the development of pre-service elementary teachers' environmental identities and the reduction of their materialistic tendencies towards the environment. In this research, which was carried out under the action research design, an action plan was prepared within the scope of moral reasoning based environmental education. This study involved 23 pre-service teachers studying at the department of elementary teaching. Qualitative data were collected using open-ended questionnaires and reflective writing forms, discussions while qualitative data were obtained using "Materialistic Tendencies Towards the Environment Scale" and "Environmental Identity Scale". Analysingthedata obtained through open-ended questionnaires carried out at the beginning and at the end of an 8-week application, related to positive environmental identity was observed to increase at the end of the study, while those related to materialistic tendencies towards the environment seemed to reduce. In this study, pre-test and post-test mean scores that pre-service elementary teachers obtained from the "Environmental Identity Scale" and "Materialistic Tendencies Towards the Environment Scale" werestatistically significant.